Tinjauan Hukum terhadap Peran Pejabat Pembuat Komitmen Pengadaan Barang dan Jasa - Poniyah, Sri; Sinaulan, Ramlani Lina; Farhana, Farhana (Jurnal Penelitian Hukum Legalitas, 2023)
Corruption in the procurement of goods and services is a serious concern in many countries, including Indonesia. In this context, the role of the Commitment Making Officer (PPK) has a significant impact on the integrity and transparency of the procurement process. This research provides a legal review of the role of PPK in corruption crimes in the procurement of goods and services in Indonesia. The method used in this research is the normative juridical approach method. The approaches used in this type of normative research are statutory approaches and conceptual approaches. Types and sources of data used as research materials primary legal materials, secondary legal materials, and tertiary legal materials.  The results of the study found that Presidential Regulation No. 12 of 2021 authorizes PPK by prohibiting the practice of bribery, but the limits of PPK's authority are regulated by Article 52 Paragraph (2) and LKPP Circular Letter No. 8 of 2020. PPK's responsibilities include aspects of administrative and civil law, with the core of criminal liability focused on procurement law violations involving abuse of authority for personal or collective gain, harming the state. PPK's criminal liability involves individual fault, subjective fault, and the role of other parties in the procurement, including the Budget User (PA) and the Budget User Authority (KPA).